2017
DOI: 10.1038/ctg.2016.67
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Transcriptomic Response of Metabolic Vitamin B12 Pathways in Roux-en-Y Gastric Bypass

Abstract: Objectives:Vitamin B12 (B12) deficiency after Roux-en-Y gastric bypass (RYGB) is highly prevalent and may contribute to postoperative complications. Decreased production of intrinsic factor owing to gastric fundus removal is thought to have a major role, but other components of B12 metabolism may also be affected. We evaluated changes in the expression levels of multiple B12 pathway-encoding genes in gastrointestinal (GI) tissues to evaluate the potential roles in contributing to post-RYGB B12 deficiency.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…Changes in the architecture of the GIT secondary to gastric fundus resection result in decreased secretion of both HCl and pepsin by the functional remnant segment. This prevents capture of vitamin B 12 from dietary sources and determines loss of food contact with intrinsic factor (IF)-producing cells, leading to cobalamin malabsorption and deficiency [120,121]. Disrupted IF secretion is currently considered the main driver of the post-surgical B 12 deficiency [121,122].…”
Section: Vitamin B 12mentioning
confidence: 99%
See 3 more Smart Citations
“…Changes in the architecture of the GIT secondary to gastric fundus resection result in decreased secretion of both HCl and pepsin by the functional remnant segment. This prevents capture of vitamin B 12 from dietary sources and determines loss of food contact with intrinsic factor (IF)-producing cells, leading to cobalamin malabsorption and deficiency [120,121]. Disrupted IF secretion is currently considered the main driver of the post-surgical B 12 deficiency [121,122].…”
Section: Vitamin B 12mentioning
confidence: 99%
“…This prevents capture of vitamin B 12 from dietary sources and determines loss of food contact with intrinsic factor (IF)-producing cells, leading to cobalamin malabsorption and deficiency [120,121]. Disrupted IF secretion is currently considered the main driver of the post-surgical B 12 deficiency [121,122]. A 2017 small-scale study, involving 20 patients submitted to RYGB, proposed that, besides IF, other molecules involved in the vitamin B 12 metabolism may be involved in the pathogenesis of its postoperative deficiency.…”
Section: Vitamin B 12mentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Aside from limiting food intake and compromising nutrient digestion and absorption, we have shown that the anatomical changes that occur following RYGB may alter the expression of intestinal genes. [11][12][13] The effect of RYGB on the metabolism of PUFAs by intestinal cells or on n-3 PUFA status remains unclear. We here consider that the restrictive and malabsorptive procedure of RYGB can decrease significantly the systemic availability of n-3 PUFAs not only by limiting their ingestion and the intestinal surface for their absorption, but also by impacting on the intestinal expression of genes involved in their endogenous synthesis.…”
Section: Introductionmentioning
confidence: 99%